MAKING ENGLISH LANGUAGE LEARNING EASIER: TEACHING LITERATURE USING CONTENT-BASED INSTRUCTION IN THE BANGLADESHI TERTIARYT EFL CLASSROOM - Farzana, Tasnia (University of Darussalam Gontor, 2023)
The main objective of this study is to determine the feasibility of CBI approaches for teaching literature in the context of EFL in Bangladesh. This paper conducts a pilot study to determine whether it is feasible to use CBI in literature classes to enhance EFL proficiency in Bangladeshi higher education. This study builds an environment in which students actively participate in literary conversations in order to acquire grammatical aspects of the target language and use them as a platform for the production of meaningful communication by combining form-focused and literature-based strategies. The pilot test involving 13 non-targeted undergraduate Bangladeshi students was undertaken to assess the lesson plans, and 20 targeted undergraduate students from Bangladesh took part in the implementation of the lesson plans for content-based instruction in a literary course. Through pre- and post-test results from pilot studies, the study examines the usefulness of content-based instruction in teaching literature to EFL students in Bangladesh as well as the effectiveness of CBI methodologies. The study integrated both quantitative and qualitative methods for data analysis. In a fully randomised study, a variety of CBI outcome factors were assessed for feasibility and importance. Teaching ESL skills in literary courses with more detailed time information for each component would be useful. Finally, content-based education generated positive outcomes and may be utilised as an effective methodology and critical help in establishing opportunities to use English, resulting in improved English language performance.